Short-range order and energetics of disordered silicon-carbon alloys - Kelires, Pantelis C. (My University, 1992)
Monte Carlo simulations, based on an empirical potential approach, have yielded detailed information about the structural and compositional short-range order as well as the energetics of disordered silicon-carbon alloys. It is found that the network of the amorphous phase deviates from an ideal tetrahedral geometry because a considerable number of carbon atoms are threefold coordinated, especially in the carbon-rich samples. Silicon, on the other hand, retains a coordination number of four. There is no phase separation. Comparing the present results with experimental observations, it is speculated that hydrogenation will promote tetrahedral carbon coordination. In the liquid phase the tendency of carbon towards low coordination dominates the structural characteristics. Silicon coordination in stoichiometric samples is much less than in pure l-Si, indicating persistence of tetrahedral order and covalent bonding. Even at high pressures (1 Mbar) carbon coordination remains lower than four, while at this pressure pure l-C is less dense than diamond. Regarding chemical ordering, the two disordered phases show a characteristic difference. The amorphous samples exhibit a significant degree of ordering (but with homopolar bonds always present), while the liquid has a random distribution of Si and C atoms. This gradual weakening of the Si-C bond is nicely explained by analyzing the total energy of the system into bond energies. The bulk modulus of the amorphous phase is found to be larger than that of c-SiC.
Keywords: Carbon; Silicon alloys; Geometry; Hydrogenation